EFEKTIFITAS PEMBERIAN KOMPOS TRICHODERMA TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT BRACHIARIA HUMIDICOLA DI LAHAN GAMBUT - Maria Erviana Kusuma; Kastalani Kastalani; Kristina Kristina (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The aims of this study is to determine the effect of giving Trichoderma Compost on the growth and production of Brachiaria humidicola grass on peatlands and to determine the dosage of Trichoderma compost which gives the best results for the growth and production of Brachiaria humidicola grass on peatlands. This research was conducted in Tanjung Taruna Village, Jabiren Raya District, Pulang Pisau Regency, from September to November 2018. This study was designed using a Completely Randomized Design (CRD) with a single treatment of various doses of compost (K), k0 = without compost, k1 = 20 tons ha-1, k2 = 30 tons ha-1 and k3 = 40 tons ha-1. The results of this study showed that giving compost had an effect on the plant height of Brahiaria humidicola grass 6 week after planting and 8 week after planting as well as crop production and 30 ton ha-1 compost giving the best production of Brahiaria humidicola on peat land.